Randomised controlled trial of fosfomycin in neonatal sepsis: pharmacokinetics and safety in relation to sodium overload. Issue 9 (25th January 2022) - Obiero, Christina W; Williams, Phoebe; Murunga, Sheila; Thitiri, Johnstone; Omollo, Raymond; Walker, Ann Sarah; Egondi, Thaddaeus; Nyaoke, Borna; Correia, Erika; Kane, Zoe; Gastine, Silke; Kipper, Karin; et al.
Abstract : Objective: To assess pharmacokinetics and changes to sodium levels in addition to adverse events (AEs) associated with fosfomycin among neonates with clinical sepsis. Design: A single-centre open-label randomised controlled trial. Setting: Kilifi County Hospital, Kenya. Patients: 120 neonates aged ≤28 days admitted being treated with standard-of-care (SOC) antibiotics for sepsis: ampicillin and gentamicin between March 2018 and February 2019. Intervention: We randomly assigned half the participants to receive additional intravenous then oral fosfomycin at 100 mg/kg two times per day for up to 7 days (SOC-F) and followed up for 28 days. Main outcome(s) and measure(s): Serum sodium, AEs and fosfomycin pharmacokinetics. Results: 61 and 59 infants aged 0–23 days were assigned to SOC-F and SOC, respectively. There was no evidence of impact of fosfomycin on serum sodium or gastrointestinal side effects. We observed 35 AEs among 25 SOC-F participants and 50 AEs among 34 SOC participants during 1560 and 1565 infant-days observation, respectively (2.2 vs 3.2 events/100 infant-days; incidence rate difference −0.95 events/100 infant-days (95% CI −2.1 to 0.20)). Four SOC-F and 3 SOC participants died. From 238 pharmacokinetic samples, modelling suggests an intravenous dose of 150 mg/kg two times per day is required for pharmacodynamic target attainment in most children, reduced to 100 mg/kg two times per day in neonates aged <7 days or weighing <1500 g. Conclusion and relevance: Fosfomycin offers potential as an affordable regimen with a simple dosing schedule for neonatal sepsis. Further research on its safety is needed in larger cohorts of hospitalised neonates, including very preterm neonates or those critically ill. Resistance suppression would only be achieved for the most sensitive of organisms so fosfomycin is recommended to be used in combination with another antimicrobial. Trial registration number: NCT03453177 . Abstract : A trial of Fosfamycin in combination with standard antibiotic therapy in newborn sepsis which established the dose that is appropriate in preterm and term neonates.